Aplikasi Media Pembelajaran Berbasis Game Drag dan Drop Mengenai Flora Dan Fauna Langka Menggunakan Metode Luther dan Computer Based Instruction - Pratama, Muhammad Ridzky; Siregar, Yunita Sari; Khairani, Mufida (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2022)
Rare flora and fauna are living things other than humans whose ecosystems must be protected because they will become extinct due to rampant poaching and destruction of ecosystems in order to create new agricultural areas. By helping of information technology and programming languages, especially existing web-based applications, there will be very many benefits. One example is the application of web-based learning media applications. Based on the existing problems, a conducting research can assist in the teaching process so that there is a sense of child growth and development to maintain the ecosystem from an early age by adopting technological advances. In designing this web-based application using the Construct 2 application by applying the Luther method and the CBI (Computer Based Instruction) method which will display audio visuals so that it can increase students' interest in learning about rare flora and fauna materials in order to maintain the ecosystem, and make the teaching process no longer find it difficult to understand the material of rare flora and fauna. The results obtained is the creation of a rare flora and fauna learning media application based on drag and drop games using the Luther and the web-based CBI (Computer Based Instruction) method by the application can help facilitate the learning process in order to maintain the flora and fauna ecosystem in nature. Keywords: Flora, fauna, Construct 2, Web, Luther Method, CBI